Local communites perception on impact of movie animation park studios as tourism development at Bandar Meru Raya Ipoh - Mohamad Hamdan, Mohamad Hamie Aqil (2019)
This study was conducted at Bandar Meru Raya Ipoh. The purpose of this study to determine local community’s perception on impact of tourism development at Bandar Meru Raya Ipoh. Specifically, it determines the social, economic and environment impacts of the development of the movie animation park studios, which is a new tourism attraction in Ipoh. The study found that local community’s perception were more positively inclined, especially for the economy and social factors while the perception towards the environment impact was balanced at 50% positive and negative impacts. In addition, the results of this study may be used by the government of the states Perak, local communities and residents to develop more tourism activities in Ipoh Perak while reducing the tourism impacts on the area and the local communities can contribute more on the tourism development at the area.